Analisis Efisiensi Ruang Perawatan Intensif dengan Menggunakan Model Data Envelopment Analysis (DEA) : Studi Kasus: Rumah Sakit Ciremai Kota Cirebon - Mutia Rane; Maula Ismail Mohammad; Lina Khasanah; Bambang Karmanto (Pusat Riset dan Inovasi Nasional, 2026)
The ICU is one of the largest clinical cost centers in hospitals due to its high demand for human resources, medical equipment, and operational costs. This situation emphasizes that intensive care unit efficiency is a multidimensional issue that cannot be assessed solely from a single aspect. This study aims to analyze the efficiency of the intensive care unit at Ciremai Hospital, Cirebon City, using the Data Envelopment Analysis (DEA) model to determine resource optimization. Analytical quantitative study with a cross-sectional design. The population in this study consisted of personnel in the ICU of Ciremai Hospital from 2023 to 2025, with total sampling applied. The input variables included the number of physicians, nurses, beds, monitors, and ventilators, while the output variables consisted of BOR, LOS, and recovered patients. The ICU input variables remained stable during the study period, while output variables fluctuated with a declining trend in BOR and LOS. The results of the Data Envelopment Analysis (DEA) indicated that all study periods achieved an efficiency score of 1.00 (efficient), with a slack value of 0.00 across all input variables.